Joshua: Jesus Son of Naue in Codex Vaticanus. By A. Graeme Auld. Pp. xxix + 236. (Septuagint Commentary Series.) Leiden and Boston: Brill, 2005. isbn 90 04 13842 0, issn 1572–3755. n.p - Salvesen, Alison ca. 20./21. Jh. (The journal of theological studies, 2006)
This is the first volume of the Septuagint Commentary Series to appear: 2–3 Maccabees and 4 Maccabees are to be published shortly. For this reason it would have been helpful to provide some introduction to the series as a whole outlining its precise purpose. Since this series has ‘competitors’ in the shape of the New English Translation of the Septuagint (NETS), the French Bible d’Alexandrie series, and the German Septuaginta Deutsch project, readers need to be told in what way the Septuagint Commentary Series aims to be distinctive.